2015
DOI: 10.4172/2470-6965.1000134
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial and Anti-hypoglycemic Properties of Siamese Neem Tree (Azadirachta indica) in Plasmodium berghei Infected Mice

Abstract: The present study has been carried out to investigate antimalarial and anti-hypoglycemic activities of leaf aqueous crude extract of Siamese neem tree (Azadirachta indica) against Plasmodium berghei infected mice. Groups of ICR mice were treated orally with Siamese neem tree extract (500, 1000, and 2000 mg/kg) after infection with P. berghei ANKA. Parasitemia and blood glucose levels were determined. At these doses, Siamese neem tree extract inhibited parasitemia in dose-dependent manner with significance (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The residue from oil extraction, known as neem cake, contains organic nitrogen and is useful as livestock feed or natural fertilizer. Numerous studies on insects have utilized neem oil (7,62,81,82). Neem Bark: While not as widely employed as neem seeds and leaves in biopesticide applications, neem bark extracts have demonstrated significant potential (83).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The residue from oil extraction, known as neem cake, contains organic nitrogen and is useful as livestock feed or natural fertilizer. Numerous studies on insects have utilized neem oil (7,62,81,82). Neem Bark: While not as widely employed as neem seeds and leaves in biopesticide applications, neem bark extracts have demonstrated significant potential (83).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Approximately 80% of the global populations relies on herbal remedies as the principal source of medicinal treatments for various illnesses [6]. Notably, certain anti-malarial medications like quinine and artemisinin, have either been derived from plants or constructed based on their chemical compositions [7].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of "Neem" have been reported to completely cure experimental malaria at 600 mg in two days, which is quite a high dose [9]. The wonder plant, Azadirachta indica, possesses anti-malarial, anti-microbial, anti-bacterial [6,8], anti-oxidant, anti-inflammatory [10], antipyretic and anti-parasitic properties [11]. Nevertheless, Las et al [12] had reported on the contraceptive effects of Neem oil which included a reduction in sperm motility.…”
Section: Introductionmentioning
confidence: 99%
“…Antimalarial activities of many local Thai plants have been reported, for example the Siamese neem tree, green tea extracts, Garcinia mangostana Linn., Phyllanthus emblica, Annona squamosa, Centella asiatica and Ipomoea pes-caprae. [8][9][10][11] The objective of this study was to determine the antimalarial activity against the P. falciparum strain TM267 of ethanol crude extracts from 20 local Thai herbs, Azadirachta indica A., Saccharu mofficinarum L., Curcuma longa L., Curcuma xanthorrhiza Roxb., Zingiber montanum, Citrus hystrix DC., Hibiscus sabdariffa L., Ocimum sanctum L., Ocimum basilicum L., Allium sativum L., Quercus infectoria, Myristica fragrans Houtt., Strychnos nux-vomica L., Salacia chinensis L., Maclura cochinchinensis Lour., Pentace burmanica Kurz., Mammea siamensis Kosterm., Vitex trifolia Linn., Plumbago indica L. and Dracaena loureiri. Interestingly, this study also examined potential antimalarial drug prediction from PfDHFR docking.…”
Section: Introductionmentioning
confidence: 99%